2006
DOI: 10.3171/spi.2006.4.5.351
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of operative and nonoperative treatment for thoracolumbar burst fractures in patients without neurological deficit: a systematic review

Abstract: Object Despite extensive published research on thoracolumbar burst fractures, controversy still surrounds which is the most appropriate treatment. The objective of this study was to evaluate the scientific literature on operative and nonoperative treatment of patients with thoracolumbar burst fractures and no neurological deficit. Methods In their search of the literature, the authors identified all poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
97
0
6

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 32 publications
1
97
0
6
Order By: Relevance
“…Although many studies have obtained good results with nonoperative treatment of thoracolumbar burst fractures [6][7][8], most authors agree that surgical treatment is required for symptomatic, unstable burst fractures [9,10]. Surgical intervention can decompress neural elements, restore vertebral body height, correct angular deformity and stabilize the spine.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have obtained good results with nonoperative treatment of thoracolumbar burst fractures [6][7][8], most authors agree that surgical treatment is required for symptomatic, unstable burst fractures [9,10]. Surgical intervention can decompress neural elements, restore vertebral body height, correct angular deformity and stabilize the spine.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with such fractures may be treated with either nonoperative or operative modalities. Nonoperative treatment may include the use of a brace, cast, bed rest, and analgesics [7,11,12,14,34,46,47]. Operative treatment usually involves instrumented intervertebral fusion, with or without spinal decompression.…”
mentioning
confidence: 99%
“…Several systematic reviews of nonoperative versus operative treatment for thoracolumbar burst fractures without a neurologic deficit have been published [18,46,48,55]. However, Dai et al [18], Thomas et al [46], and van der Roer et al [48], based their conclusions primarily on descriptive summaries, included observational studies, and did not perform meta-analyses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies on neurologically intact patients have not shown any differences in the long-term functional results among patients with this type of lesion, independent of whether they underwent surgical treatment or not (2,3,10) . However, the surgical method is generally proposed for patients whose fractures have led to loss of 50% of the height of the vertebral body and kyphosis greater than 30°, because of inadequate functional results.…”
Section: Discussionmentioning
confidence: 99%